IDENTIFIKASI JENIS MANGROVE PADA KAWASAN RESTORASI EKOSISTEM MANGROVE DI DESA KEUDE PANGA KECAMATAN PANGA KABUPATEN ACEH JAYA - Hilham Mulia Riski; Neneng Marlian; Nabil Zurba (Journal of Aceh Aquatic Sciences, 2021)
This study aimed to identified mangrove species, calculated the total number and composition of mangroves, and the structure of zonation mangroves at the mangrove relocation area in Keude Panga Village, Panga District, Aceh Jaya Regency. The study was carried out on April 2021, for one month with two replications. The research method was the survey method, namely directed observation to research location. A sampling of mangroves used the quadratic transect method, which was divided into 3 transect points with the categories of tree plots measuring 10 m x 10 m, sapling plots with 5 m x 5 m, and the seedling plots measuring 1 m x 1 m. Data analyzed of the total number and composition of mangroves used Microsoft Excel 2010 and zonation of mangrove analysis was carried out descriptively. The results showed on the research at both stations founded 3 species of true mangrove and 1 species of scrub respectively, namely Rhizhopora mucronata (19% sapling level), Rhizhopora apiculata (34% sapling level), Nypa fruticans (47% tree level), Acrostichum aureum (or 100% shrub category) and Rhizhopora mucronata (23 individuals or 37% sampling level), Rhizhopora apiculata (15 individuals 20% sapling level), Nypa fruticans (36 individuals or 49% tree level), Acrostichum aureum (100% shrub category). Structure zonation of mangrove vegetation is composed of 3 species of mangroves, namely Rhizhopora mucronata which was located closest to the sea, Rhizhopora apiculata was in the middle of the mangrove ecosystem, and Nypa fruticans was a pioneer mangrove located close to the mainland.